Changes in Retinal Ganglion Cell (RGC) and Retinal Nerve Fiber Layer (RNFL) Thickness in Children with Type 1 Diabetes Mellitus at Dr. M. Djamil General Hospital, Padang, Indonesia - lonanda, Gama Agusto; Kemala Sayuti; Havriza Vitresia; Hendriati; Andrini Ariesti; Weni Helvinda (HM Publisher, 2024)
Background: Type 1 diabetes mellitus (DM) is a chronic metabolic disorder that causes hyperglycemia and increases the risk of morbidity and mortality. Diabetic retinopathy, a microvascular complication that often occurs in DM patients, can cause visual impairment and even blindness. Regular eye examinations are important for early detection of diabetic retinopathy. Optical coherence tomography (OCT) is a non-invasive method that can be used to measure the thickness of retinal layers, including RGC and RNFL. It is thought that thinning of the retinal layer can be a sensitive biomarker in detecting diabetic retinopathy in type 1 DM patients. This study aims to determine changes in RGC and RNFL thickness in children with type 1 DM. Methods: This cross-sectional design analytical observational study was conducted at the eye polyclinic of Dr. M. Djamil General Hospital Padang in November 2023-March 2024. A total of 46 eyes from 46 people, divided into two groups: the type 1 DM group and the control group, were recruited in this study. RGC thickness was measured using AS-OCT GC-IPL thickness analysis and RNFL with optic disc RNFL thickness analysis. Data analysis was carried out using the unpaired T-test. Results: The results showed RGC depletion in the type 1 DM group (RGC 83.48 ± 3.75) compared to the control group (RGC 86.70 ± 4.87) with a value of p = 0.016 (p < 0.05). There was no statistical difference in RNFL thickness between the type 1 DM group (RNFL 102 ± 11.80) and the control group (RNFL 100.96 ± 10.97) with a value of p = 0.581 (p> 0.05). Conclusion: This study found RGC thinning in type 1 DM patients, but did not find differences in RNFL thickness between the two groups. This RGC depletion is thought to be caused by apoptosis of retinal neuronal cells due to chronic hyperglycemia. Examination of RGC thickness with OCT can be developed as an early detection of diabetic retinopathy in children with type 1 DM.